A Monotone Finite Volume Scheme with Second Order Accuracy for Convection-Diffusion Equations on Deformed Meshes. (Communications in Computational Physics, 2018)
In this paper, we present a new monotone finite volume scheme for thesteady state convection-diffusion equation. The discretization of diffusive flux [33]is utilised and a new corrected upwind scheme with second order accuracy for thediscretization of convective flux is proposed based on some available informations ofdiffusive flux. The scheme is locally conservative and monotone on deformed meshes,and has only cell-centered unknowns. Numerical results are presented to show thatthe scheme obtains second-order accuracy for the solution and first-order accuracy forthe flux.